2020
DOI: 10.1155/2020/5681296
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Indirect Bilirubin Level and Insulin Sensitivity: Results from Two Independent Cohorts of Obese Patients with Impaired Glucose Regulation and Type 2 Diabetes Mellitus in China

Abstract: Background. Serum bilirubin is an endogenous antioxidant that has protective effects against obesity-related metabolic diseases. Objectives. This study aimed to evaluate the characteristics of total bilirubin (TBIL), direct bilirubin (DBIL), and indirect bilirubin (IBIL) and their relationships with insulin sensitivity in obese patients with impaired glucose regulation and type 2 diabetes mellitus (IGR/T2DM) in China. Patients and Methods. Cohort 1 comprised obese patients (n = 71) was divided into the IGR/T2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
1
11
0
1
Order By: Relevance
“…Diabetic patients are often characterized by more complex, extensive, and diffuse coronary lesions. As introduced in the beginning, abnormal bilirubin levels were observed in the diabetic patients (16,17). Together with our studies, DB was a surrogate biomarker of oxidative and inflammatory responses, the common mechanisms in both ACS and diabetes.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Diabetic patients are often characterized by more complex, extensive, and diffuse coronary lesions. As introduced in the beginning, abnormal bilirubin levels were observed in the diabetic patients (16,17). Together with our studies, DB was a surrogate biomarker of oxidative and inflammatory responses, the common mechanisms in both ACS and diabetes.…”
Section: Resultssupporting
confidence: 74%
“…Oxidative stress exerts a great impact on insulin resistance, which raises a question on whether bilirubin plays a role in this pathway (15). A study in obese patients with type 2 diabetes found that bilirubin acted as a protective factor in insulin resistance (OR = 0.744, 95% CI: 0.590-0.938, p = 0.012) (16). Nevertheless, an interesting result was also observed in that TB, DB, and indirect bilirubin levels were higher in the diabetes group than in the normal metabolism population.…”
Section: Introductionmentioning
confidence: 94%
“…The serum total bilirubin concentrations in the present study were inversely associated with the insulin resistance risk. Previous studies also reported that serum total bilirubin concentrations are inversely related to the MetS risk in various ethnic groups [ 43 , 44 , 45 , 46 ]. It might be associated with the cholesterol metabolism in the liver.…”
Section: Discussionmentioning
confidence: 86%
“…However, these associations were weak and of doubtful clinical relevance. An inverse association between serum bilirubin and HOMA-IR has been, nonetheless, previously reported in adults and children [57,58].…”
Section: Discussionmentioning
confidence: 95%